Improving Justice for American Indian and Rural Victims of Crime Through Community-Engaged Research - Heer, Brooke A. deerfasserIn (Journal of contemporary criminal justice, 2021)
Community-engaged research can be effective in directly improving justice for individuals and communities, and to guide policies and practices. Given the challenges to accessing some populations of interest, such as with rural victims of crime, community-engaged approaches provide a means to support ethical and culturally competent research that can improve justice in a meaningful way. In this article, we discuss a collaborative research partnership between academic researchers and a victim service agency that sought to connect rural victim advocacy with a data-driven research methodology for improved justice delivery in two communities with differing rural dynamics. Researchers and practitioners can benefit from recognizing the unique, yet varied, victimization experiences within rural communities, and an understanding of this variability among rural victims and contexts can inform justice practice. We provide best practice recommendations from both researcher and practitioner perspectives for the successful implementation of a project that serves victims in the community and through policy. Implications for justice-related policy and practice for rural and American Indian crime victims are discussed.